Transition From Secondary School to EMI University: Understanding Challenges and Language Strategy Use of Undergraduate Students in Kazakhstan - Toktarova, Aiza (Nazarbayev University Graduate School of Education, 2024)
The increasing significance of English as the language of global commerce, tourism and politics has led to many educational institutions worldwide adopting English as the medium of instruction (EMI) in recent decades. There are few studies that examine how Kazakhstani students view and experience the transition from their native language (L1) schooling to EMI universities in Kazakhstan. This qualitative study aims to fill this gap by investigating the challenges, both linguistic and academic, faced by ten first-year students at a prestigious EMI university in Kazakhstan. All the students participating in this study came from mainstream schools where Kazakh or Russian was the main language of instruction. The study also attempted to capture these participants’ strategic learning efforts used to confront their diverse challenges at the EMI university. Guided by Spolyky’s (2004) theoretical framework on language policy and Oxford’s (1990) classification of LLSs, this qualitative study sought to answer the following main and sub-research questions: 1) How do Kazakhstani first-year students perceive their experience at one of the highly selective EMI universities in Kazakhstan? a) What motivated the participants’ to join this EMI university? b) What were the participants’ academic and linguistic challenges at this EMI university? c) What strategies did the participants use to cope with these challenges? The data were collected from ten first-year undergraduate students studying at one EMI university in Kazakhstan, using two qualitative research methods: a written narrative and individual semi-structured interviews. The study found that the participants’ challenges at the EMI university were classified into three interrelated categories: language-related, academic, and individual. To encounter these challenges, the participants deployed a host of effective strategies, including both direct (memory, cognitive, compensation) and indirect (metacognitive, affective, social) strategies. Based on the findings of this qualitative study, practical and pedagogical implications were presented, by assuring the importance of providing students with psychological support, integrating academic English into the mainstream school curriculum, and promoting university writing centers. The study also offers implications for policymakers in Kazakhstan and areas for further research, including the emotional landscape of EMI and fair access to highly selective EMI universities.
Keywords: Medium of instruction (MOI), English-medium instruction (EMI), academic challenges, language-related challenges, transition period, language learning strategies (LLSs); type of access: gated access